The Sixties in Pictures - Lescott, James (Bath Parragon, 2007)
"From the assassination of JFK to the massacre at Sharpeville, from the building of the Berlin Wall to the first manned space flight, from the March on Washington to Beatlemania, from the Cultural Revolution to the coming of Bond. Here are the Swinging Sixties in all their dizzy detail."--Publisher description.
Include Illustrations and Index
Keywords: Nineteen sixties